“Unity and Refinement”. Paths and Quests for Organizational and Ceremonial Unity in the First Half of the 20th Century - PAP, Ferenc (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
This article explores the efforts of the Hungarian Reformed Church in the first half of the 20th century to achieve uniformity and refinement in its worship practices. The desire for a unified Hungarian Reformed worship service had been a hallmark of previous centuries, leading to a long journey of development in the 20th century. The standardization of the liturgical praxis aimed to create a sense of shared identity and eliminate historical variations in regional worship practices and customs. The movement for liturgical unity had been ongoing for centuries, with earlier attempts including church district agendas published in the 19th century. The publication of the Liturgical Book [Istentiszteleti Rendtartás] in 1930, which is the first official Agenda for the whole Reformed Church in Hungary, marked a culmination of efforts towards liturgical unity. The paper highlights the tension between achieving uniformity and preserving diversity within a religious tradition.